Harmonic functions of general graph Laplacians - Hua, Bobo; Keller, Matthias (Calculus of variations and partial differential equations, 2014)
We study harmonic functions on general weighted graphs which allow for a compatible intrinsic metric. We prove an L p Liouville type theorem which is a quantitative integral L p estimate of harmonic functions analogous to Karp’s theorem for Riemannian manifolds. As corollaries we obtain Yau’s L p -Liouville type theorem on graphs, identify the domain of the generator of the semigroup on L p and get a criterion for recurrence. As a side product, we show an analogue of Yau’s L p Caccioppoli inequality. Furthermore, we derive various Liouville type results for harmonic functions on graphs and harmonic maps from graphs into Hadamard spaces.